Chart of North and South America, including the Atlantic and Pacific Oceans, with the nearest Coasts of Europe, Africa, and Asia [sheet 1] - Jefferys, Thomas, d. 1771; Green, John fl. 1730-1753 (Robert Sayer and John Bennett (Firm), 1775)
18th century Copper engraving handcolored with watercolor. Mounted lon linen. Outline color. Relief shown pictorially. Top portion of 3-sheet map. This map was issued as 6 sheets (in this case 3 sheets, but each of those is a joined pair). The first sheet is titled as the map, however each sheet also has its own headings. The UW holds only the first two sheets out of three. Printed along the top border: "A Chart of North and South America, including the Atlantic and Pacific Oceans, with the nearest Coasts of Europe, Africa, and Asia." Printed along the left side of the bottom edge: "Chart containing part of the Icy Sea with the adjacent Coast of Asia and America." Printed along the right side of the bottom edge: "Chart comprizing Greenland with the Countries and Islands about Baffin's Bay and part of Hudsons Bay." Printed beneath bottom left border: "Publish'd according to Act of Parliament, 10 June 1775, by Robt. Sayer & J. Bennett, No. 53 in Fleet Street." Printed beneath title above Baffin's Bay is a comparative table showing comparisons of observations of exact geographic locations with dates and names of observers. Printed beneath "Northern Ocean" is a table of "Latitudes observed by Captn. Behring on the Coast of Siberia." Printed beneath this table: "From the above Table it appears that the Coast of Asia extends 60 Degrees more East than the Maps & Charts of Moll and 53 more than those of Senex place it; so that they omit a vast extent of country, in like manner they curtail the North West Coast of America 20 Degrees in Longd. and 20 in Latd. so making the distance between the two Continents more than 1000 Leagues when it is less than 100." Printed in the northwest region of North America at latitude 72 degrees north and longitude 125 degrees west: "Messrs. Bellin and Bruckner place erroneously Captn. Behrings Isle, where he was stranded and died, here about, in Lat. 72 degrees Long. 125 degrees and continue the Coast from California thither." Printed beneath a line marking the Polar Circle in the northwest region of North America: "These parts, as yet wholly unknown are filled up, by Mssrs. Buache and Del'Isle, with the pretended Discoveries of Adml. De Fonte and his Captains in 1640." Labels the far western coast "Great Continent" and printed beneath this region: "[Russ? Stachtannitada] from whence the Russians fetch beautiful Furs and seen by Captn. Spangenberg in 1728." Printed above Asia: "The N. E. end of Asia being part of Siberia is Drawn from Capt. Behring (or Beering) own Map of his Discoveries improved from the Map of the New Northern Archipelago. Published at Petersburg in 1774 by Mr. J. Von Staehlin, Secretary to the imperial Academy." Printed at about 85 degrees west longitude along bottom edge: "Note. The North and South Tides meet, below Marble Island, & are always equal on the same days; so that neither of them can come from the Pacific Ocean, whose Distance likewise of above 430 leagues hath long cry'd aloud that there is no Passage at least for Ships frm. Hudsons Bay." Printed in center of Baffin's Bay: "This noble Discovery was made in Search of a N.W. Passage, by Capt. Robt. Bilot, conducted by Willm. Baffin in 1616 not 22: Neither did Muuck ever enter this Bay or give it the Name of Christians Sea as some late Charts and Maps English as well as French would have it." Shows course of Russian ships heading to Kamschatka. Also shows route followed by Lieutenant Sindo in 1768 and Captain Bering in 1728. Depicts route that Robert Bilot took with William Baffin in 1616 in search of a Northwest Passage around what is now Baffin's Bay. Shows a line marking "the Polar Circle" at about 67 degrees north latitude. Depicts Iceland, Greenland, "Arctic Lands," Baffin's Bay, the northern part of Hudson's Bay, "Prince William's Land," "New North Wales," Alaska as "Alaschka", the Bering Strait as "Behring's Straits," and a body of water between Asia and the modern-day Aleutian Islands called the "Sea of Anadir." Shows northwestern tip of Russia. Illustrates areas where Eskimo live. Of note, shows Greenland as connected to North America. Prime Meridian: London and Isle of Ferro. Scale c.a. 1:5,5000,000. Thomas Jefferys (c.a. 1710-1771) was one of the most significant English cartographers of the eighteenth century. Working as an engraver, geographer and publisher, he created some of the most important English and American maps of his day. He was appointed Geographer to Frederick Prince of Wales in 1748 and later served as Geographer to George III. One of his first maps is a "Plan of London and Westminster" (1732). His other works include Kitchin's "Small English Atlas" (1749), ""Map of Staffordshire" with Parson and Bowles (1747), engravings for Salmon's "Geography" (1749), a last published edition of Saton's "Atlas" (1752), and "Maritime Ports of France" (1761). Between 1751 and 1768, he published a number of other maps, mainly of America and the West Indies including Fry and Jefferson's "Virginia" (1751), "Nova Scotia" (1755), De Braham's "Carolina"' (1757), "St. Lawrence" by Captain cook (1760), a volume on "Spanish Islands and West Indies' (1762), and "Topography of North America and the West Indies" (1768). He also surveyed and engraved "county maps of Bedfordshire" (1765), "Hampshire" (1766), "Oxfordshire" (1766-7), "Durham and West" (1768), "Buckinghamshire" (1770) and "Yorkshire" (1767-70). Despite his prolific nature, Jefferys found himself bankrupt in 1765. Many of his plates were acquired by Robert Sayer who published much of Jeffreys' work in "North American Atlas" (1775), "West Indian Atlas" (1775) and "North American Pilot" (1775). Jefferys later partnered with William Faden who received Jeffreys' shop when he died in 1771 (Tooley 335). John Green (fl. 1730-53, d. 1757) constructed many maps and globes. His name was a pseudonym for Braddock Mead. His works include "North and South America" (6 sheets) for Jefferys (1753) and a second edition of the map in 1768 (Tooley, 262). Robert Sayer (1725-1794) was a publisher and map and print seller who published much of his contemporaries' work including the work of Thomas Kitchin, Belin and d'Anville (Moreland and Bannister, 172). He worked with Philip Overton beginning in 1745 utnil Overton died in 1751. Sayer then continued to work on his own. He published Rocque's small "British Atlas" (1753), "map of Atlantic" (1757) and "Large English Atlas" (1760). He later collaborated with Herbert and reissued many works by John Senex (?-1740). After cartographer, Thomas Jefferys, went bankrupt, Sayer took some of Jeffreys' assets and with Jefferys published "General topographic map of North America and the West Indies" (1768) and "Middle British Colonies in America" (1768, 1775). In 1770, Sayer was joined by John Bennett. In 1771, Jefferys died and most of his business passed to William Faden while some of his plates stayed in Sayer's hands. Sayer and Bennet then published "General Atlas" (1773), "North American Atlas' (1775), "North American Pilot" (1775-6), "American Military pocket Atlas" (1776), "West India Atlas" (1775), and "Complete Channel Pilot" (1781). In 1781 Bennett retired and then died in 1787. Sayer continued to work on his own until his own retirement in 1792. He then sold his plates and business to Robert Laurie and James Whittle (Tooley, 561). This map was first published June 10, 1775 though it was created earlier by Jefferys with the aid of John Green (fl. 1730-1753). Each section of the map seems to be a different size. The map shows the legends based on Fonte and Fuca. Wagner notes that this map refers to the Pérez's expedition in 1774 in two legends, the first describing "white and fair Indians" and the second stating "inhabitants which go naked" (Wagner, 343, entry 649). Source(s): Moreland, Carl and David Bannister. "Antique Maps: A Collector's Handbook." New York: Longman Group, Ltd., 1983. Tooley, Ronald Vere. "Tooley's Dictionary of Mapmakers." Hertfordshire: Map Collector Publications Limited, 1979. Wagner, Henry R. "The Cartography of the Northwest Coast of America to the year 1800 Volume 2." Berkeley: University of California Press, 1937.